1982
DOI: 10.1136/jnnp.45.8.743
|View full text |Cite
|
Sign up to set email alerts
|

Failure of postural manoeuvres to prevent lumbar puncture headache.

Abstract: SUMMARY Diagnostic lumbar puncture was performed on 76 neurological inpatients. They were randomly allocated to one of four bed rest positions for four hours following the procedure (supine and horizontal, prone and horizontal, supine with head-down tilt and prone with headdown tilt) after which they were allowed to get up. There was no substantial or significant difference in the incidence of headache between the four groups. Expectation of headache did not appear to be an important factor in its development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Similarly, because we did not require rest in the supine position after LPs, we could not evaluate the potential influence of this intervention. Other studies have found that rest after LP does not prevent PDPH 24‐27 . All LPs in our study were performed with 22‐gauge, atraumatic needles, as opposed to the traditional, cutting‐edge (Quinke) needle.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, because we did not require rest in the supine position after LPs, we could not evaluate the potential influence of this intervention. Other studies have found that rest after LP does not prevent PDPH 24‐27 . All LPs in our study were performed with 22‐gauge, atraumatic needles, as opposed to the traditional, cutting‐edge (Quinke) needle.…”
Section: Discussionmentioning
confidence: 94%
“…Manual review of abstracts and/or full texts identified 22 unique references evaluating the relationship between CSF volume and/or pressure measurements and PDPH incidence (Fig. ) . The references included analysis of V (n = 14), OP (n = 11) and/or CP (n = 4) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Alpers felt a relationship between elastance and PDPH existed, but did not conduct a formal comparison . Hilton‐Jones et al comments on the mean change in pressure after removal of 10 mL of CSF as statistically similar in patients with and without headache . Therefore, both Alpers and Hilton‐Jones evaluated E, although did not comment on it by name.…”
Section: Discussionmentioning
confidence: 99%
“…PLPHA is related to a number of factors, including young age, female gender, headache history, small body mass index and pregnancy (10). Despite these uncontrollable factors, there are also some variables which can influence the incidence of PLPHA such as needle size (should be less than 20 gauge), bevel orientation and the number of dural punctures (11)(12)(13). The position of the patient after LP, the volume of fluid removed during LP and hydration following LP have all been found to affect the incidence of PLPHA (10,13,14).…”
Section: Discussionmentioning
confidence: 99%